Scenarios for Iran’s Cyberspace Issues in 1395sh - Mohammad Mahdi Mowlaei; Hamed Talebian; Hamid Abedi (مطالعات رسانه‌های نوین, 2017)
In this article, we will present some scenarios for Iran’s cyberspace issues in 1395sh (equal 20 March 2016 – 20 March 2017 in Gregorian calendar). Scanning of Iran’s environment, showed 195 variables have higher priority than average. These variables are recognized by gathering data from different methods and getting expert viewpoints in various fields, in '1395sh Iran’ Futures Studies’ project. Among them there are seven variables defined in cyberspace and some other variables set in relation with cyberspace. In this article, we constructed seven hypotheses for Iran, based on seven key variables and other related variables, then, probabilistic cross impact analysis method is used to create scenarios. To do so, we measured the occurrence probability of each hypothesis by expert opinion firstly, and we estimate the cross impact of each hypothesis on others in the condition of occurrence or failure secondly, until conditional probability matrixes are formed. To analysis of data, ‘Smic-Prob Expert’ software which is a tool in French school of strategic foresight (La Prospective) is used. 64 possible scenarios for Iran’s cyberspace along with occurrence probability of each are estimated with software. The Findings indicate that scenarios based on status quo with the most probabilities do not draw a desirable future for Iran’s cyberspace in forthcoming year.